“This Is Not Gym”: Enacting Student Voice Pedagogies to Promote Social and Emotional Learning and Meaningful Physical Education - Howley, Donal; Dyson, Ben; Baek, Seunghyun; Fowler, Judy; Shen, Yanhua (Frontiers in Sports and Active Living, 2021)
The purpose of this study was to explore learners' experiences enacting youth/student voice pedagogies (SVP) to promote Social and Emotional Learning (SEL) and meaningful physical education (MPE) in an alternative education setting. Drawing on social constructivist learning theory in understanding and implementing a MPE approach, and a systemic framework for SEL, two research questions guided the research process: (1) How did students interpret and enact these pedagogies? (2) What contribution did the enactment of these pedagogies have in promoting SEL and MPE? This study implemented a qualitative case study design framed by a participatory action research (PAR) approach spanning 12 weeks from February to May 2021. Participants in this study included 16 ninth grade alternative high school students (eight girls/eight boys) aged 14–15 who had just returned to face-to-face learning in January 2021 for the first time following COVID-19. A range of traditional and innovative participatory qualitative research methods including focus group interviews, students' personal biographies, timelines, digital and written reflections, photovoice, and class artifacts were utilized. The Miles, Huberman, and Saldana Framework for Qualitative Data Analysis was implemented involving both deductive and inductive combinations of comparative and thematic analysis. The following themes were constructed: Making responsible decisions; unearthing and sharing mixed emotions; picturing physical activity beyond the classroom; recognizing the role of relationships; considering challenge and competence; and, pursuing meaning. Findings demonstrate how enacting SVP can lead to the development of students' SEL and MPE experiences complimenting multiple learning domains. We call for further embedding of SVP capturing students' physical activity and movement experiences inside and outside of PE in teacher education and professional development that helps teachers and their students make sense of, shape, influence, and enact more MPE and physical activity learning experiences.